The Analytics Paradigm: Balancing Innovation and Ethics in a Data-Centric World - Teena Choudhary, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines data analytics's profound and multifaceted influence on contemporary society, exploring its transformative impact across various sectors and the challenges it presents. By synthesizing current research and case studies, we demonstrate how data analytics enhances decision-making through personalization and predictive insights, drives innovation in business and technology, and improves public services, particularly in healthcare and urban planning. The article also critically addresses the ethical implications and privacy concerns associated with the proliferation of data-driven approaches, including data security, algorithmic bias, and fairness. As data analytics continues to reshape societal structures and individual experiences, this article argues for a balanced approach that maximizes its potential benefits while mitigating risks. Our analysis concludes by considering the long-term societal implications of this data revolution, emphasizing the need for adaptive policies, education, and ethical frameworks to guide the future development and application of data analytics in an increasingly connected world.
Keywords: Data Analytics; Societal Transformation; Ethical Implications; Innovation; Decision-Making